DEPENDENCE OF MILK PRODUCTION OF MONBELYARD COWS ON THE CHARACTERISTICS OF BODY STRUCTURE (European Journal of Interdisciplinary Research and Development, 2022)
This article provides information on the characteristics of increasing the weight of cows in the direction of milk productivity in herds and improving the efficiency of using cows by selecting and mating the Montbelyard cows brought from France, taking into account the types of body structure.